2019
DOI: 10.1101/775098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GWAS and Fine-Mapping of Livability and Six Disease Traits in Holstein Cattle

Abstract: Background: Health traits are of significant economic importance to the dairy industry due to their effects on milk production and associated treatment costs. Genome-wide association studies (GWAS) provide a means to identify associated genomic variants and thus reveal insights into the genetic architecture of complex traits and diseases. The objective of this study is to investigate the genetic basis of seven health traits in dairy cattle and to identify potential candidate genes associated with cattle health… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…We collected GWAS summary statistics of 45 complex traits in cattle [24,76]. We generally grouped these 45 complex traits into 5 categories, including reproduction (n = 12), production (milk-relevant; n = 6), body type (n = 17), health (immune-relevant; n = 9), and feed efficiency (residual feed intake, RFI; n = 1) traits.…”
Section: Gwas Enrichment Analysis Based On Tissue-specific Histone Marksmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected GWAS summary statistics of 45 complex traits in cattle [24,76]. We generally grouped these 45 complex traits into 5 categories, including reproduction (n = 12), production (milk-relevant; n = 6), body type (n = 17), health (immune-relevant; n = 9), and feed efficiency (residual feed intake, RFI; n = 1) traits.…”
Section: Gwas Enrichment Analysis Based On Tissue-specific Histone Marksmentioning
confidence: 99%
“…Details of the singlemarker GWAS for body type, reproduction, and production traits using 27,214 US Holstein bulls were presented previously [24]. GWAS for health traits using~10,000 bulls could be found in [76], while GWAS for feed efficiency using 3947 Holstein cows (i.e., RFI) were described by Li et al [77]. For human GWAS data, we obtained the summary statistics for 58 complex traits with an average sample size of 128,848 and an average SNP number of 5,905,874.…”
Section: Gwas Enrichment Analysis Based On Tissue-specific Histone Marksmentioning
confidence: 99%
“…These genes were located within the top QTL of ketosis on BTA14 (Fig. 4 c) [ 10 ]. Furthermore, we found that these five candidate genes were also associated ( P < 0.05) with DSAB and livability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained summary statistics of single-marker GWAS (n ≈ 10,000) for ketosis and five health traits in cattle, which was described previously [10]. Livability as a composite trait is correlated with disease traits, reflecting a cow's overall ability to stay alive in a milking herd by measuring the percentage of on-farm deaths per lactation [10]. DSAB, highly associated with KETO, occurs when the abomasum fills with gas and moves from the floor to the top of the abdomen.…”
Section: Single-maker Gwas and Gwas Signal Enrichment Analysismentioning
confidence: 99%
See 1 more Smart Citation